Measuring Tourist's Motivations for Consuming Local Angkringan Street Food in Yogyakarta, Indonesia - Yusuf, Mohamad (Journal of Indonesian Tourism and Development Studies, 2017)
The purpose of this study was to examine the tourist motivations for consuming local angkringan street food in Yogyakarta city, Indonesia. We distributed questionnaires to 1,514 domestic tourists from several provinces in Indonesia visiting 42 angkringan spots to determine the significance of five different motivations: cultural experience, sensory appeal, media exposure, excitement and health concern. A Confirmatory Factor Analysis was used to analyze the data. A remarkable finding showed that the items belonging to the interpersonal dimension were not grouped in one factor. The Sensory appeal has the highest level of agreement among the tourists, followed by the cultural experience. The health concern has the lowest level of agreement, which is slightly lower than the excitement motivation.Keywords: Angkringan, Food Tourism, Indonesia, Street Food, Types of Tourist Motivation.